The Brugada Type 1 Electrocardiogram and Ventricular Tachycardia With High-Dose Amitriptyline - Chow, Ji-Jian; Kaza, Nandita; Varnava, Amanda (JACC. Case reports, 2021)
A 32-year-old woman with anorexia nervosa experienced ventricular tachycardia while on therapeutic-dose amitriptyline despite normal blood tests, imaging, and intracardiac recordings. Electrocardiograms over several years featured the Type 1 Brugada pattern. Careful electrocardiogram monitoring should be made if using high doses of amitriptyline, especially in those with low body weight. (Level of Difficulty: Intermediate.) [Display omitted]